2012
DOI: 10.1016/j.jaci.2012.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Ambient pollen concentrations and emergency department visits for asthma and wheeze

Abstract: Background Previous studies report associations between aeroallergen exposure and asthma exacerbations. Aeroallergen burdens and asthma prevalence are increasing worldwide and are projected to increase further with climate change, highlighting the importance of understanding population-level relationships between ambient pollen concentrations and asthma. Objective To examine short-term associations between ambient concentrations of various pollen taxa and emergency department (ED) visits for asthma and wheez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
127
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 26 publications
7
127
3
Order By: Relevance
“…Experimental studies have found reduced lung function and increased pulmonary inflammation in subjects with asthma exposed to pollen (57,58). Numerous studies in temperate climates have found increases in asthma and wheeze-related ED visits in association with high pollen concentrations (59)(60)(61)(62). Some studies have linked asthma outbreaks to thunderstorms with peaks in allergen release (51,52,63).…”
Section: Aeroallergen (Pollen) and Climate Changementioning
confidence: 99%
“…Experimental studies have found reduced lung function and increased pulmonary inflammation in subjects with asthma exposed to pollen (57,58). Numerous studies in temperate climates have found increases in asthma and wheeze-related ED visits in association with high pollen concentrations (59)(60)(61)(62). Some studies have linked asthma outbreaks to thunderstorms with peaks in allergen release (51,52,63).…”
Section: Aeroallergen (Pollen) and Climate Changementioning
confidence: 99%
“…In addition to grasses, other pollens, such as Oleaceae, Amaranthaceae, Cupressaceae, Asteraceae, and Urticaceae, play a significant clinical role [2,3]. In North America, there are pollen regions coincident with European ones with the added complexity of greater tree diversity and a high incidence of ragweed pollinosis [4,5]. Ragweed pollinosis was exported at the beginning of the twentieth century to central Europe and has steadily increased since then [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism which is leading to these consequences could be: a) because of higher temperature we could face a longer pollen seasons (it seems that if the pollen concentrations remain at high value for several consecutive days then people predisposed to allergic diseases and patients with asthma could develop a full allergic response) (Darrow et al, 2012); b) wet conditions and especially thunderstorms (which are increasing because of climate change) will produce a rupture of pollen grains and release smaller part of their content, these smaller parts are respirable particles (0.5-2 μm) and could go to lower airways and trigger an asthma attack (grass pollens, particularly, after rupture by osmotic shock will release a high quantity of paucimicronic allergenic particles) (D' Amato, 2011;D' Amato et al, 2013); c) wind speed (could trigger production and dissemination) and transition of cold fronts (cold air induce bronchoconstriction in asthmatic patients); because of environmental changes, land use and long transportation allergenic pollens could arrive in new areas and will induce new sensitizations in people with atopic predisposition who did not have prior allergies to that type of pollen (Cecchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%